PENGARUH POLA ASUH OTORITER TERHADAP ETIKA KOMUNIKASI SISWA DI SMA SWASTA ISTIQLAL DELI TUA - Widyanti, Nur; Zulkarnaen, Iskandar; Hutasuhut, Dina Hidayati; Syaimi, Khairina Ulfa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Individual behavior is the result of a long process since childhood, one of which is influenced by parenting. Parenting is the way parents educate, guide, and interact with children that shapes their personality and communication ethics in the future. Authoritarian parenting, characterized by strict control, one-way communication, and lack of freedom for children to express themselves, can have a negative impact on children's psychosocial development, including communication ethics. This study aims to determine the effect of authoritarian parenting on students' communication ethics at Istiqlal Deli Tua Private High School. The method used is quantitative with simple linear regression. The sample consisted of 32 students of class XI who were selected using purposive sampling technique. The analysis results show a constant value of 178.602, a regression coefficient of -0.819, and a significance of 0.023 < 0.05. This indicates that the higher the applied authoritarian parenting, the lower the students' communication ethics. This finding confirms the importance of open and supportive parenting in shaping ethical and effective communication skills